Estratégias de controle repetitivo para aplicação em sistemas de alimentação ininterrupta de energia - Gnoatto, Claudio Lucas (2011)
This work presents an analysis, design and implementation of repetitive control strategies applied to uninterruptible power supplies (UPS) systems. At the beginning, a literature review of the main controllers concerning this purpose is shown. A global vision of UPS systems with focus on different topologies is made and the project of an inductive capacitive filter (LC) is presented where the goal is to reduce harmonic content due to the inverter switching. After that, a control strategy is presented. In this strategy a feed forward term is used to generate the wave form shape of the output voltage and a Proportional Derivative (PD) controller is introduced to compensate non cyclic disturbances. For the compensation of cyclic disturbs some repetitive control techniques are analyzed and implemented. The inclusion of these controllers provides a good performance for the output system, however, when the system is exposed to interferences, the dynamic characteristics of these controllers are affected. Modifications are presented to make the system less susceptible for high frequencies noise and aperiodic disturbs. In addition, a repetitive controller with gain adaptation is proposed with sufficient robustness to obtain a good voltage regulation even in the presence of aperiodic disturbances and electromagnetic interferences. Finally, the implementation of a flexible platform is presented, based on PWM inverter controlled by a digital signal processor with data acquisition and generation PWM peripherals, DSP TMS320F28335. From this platform, experimental results for a monophasic UPS prototype was obtained, which ones prove the performance of the control techniques presented and proposed.